Home-Workplace Separation in Kingston: The Legal and Medical Professions — Past, Present and Future - Tunbridge, J. (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1982)
Following an earlier discussion of the evolving location of doctors in Kingston, the present article compares the medical with the legal profession, as a further step towards understanding the mechanics of the home-workplace separation process. Markedly different timing and spatial patterns are identified, pointing to the dangers of simplistic assumptions concerning residential decentralization; and some reasons for differences among these and other occupational groups are advanced, as a contribution towards unravelling the complexities of urban social evolution. Possible future changes in the currently decentralized residential distributions are considered in the light of the contemporary trend towards inner city revitalization.